Structural and diagenetic controls on reservoir quality in tight siliciclastic and carbonate rocks - Becker, Ivy (KIT Scientific Publishing, 2018)
Upper Carboniferous (Westphalian C/D) fluvial sandstones and Zechstein Ca2 (Stassfurt, second cycle) carbonates represent two important hydrocarbon reservoir units in NW Europe. A better understanding of reservoir quality variations and their spatial variability is crucial to develop successful exploration strategies. In fluvial Westphalian C/D sandstones and Ca2 carbonate reservoirs, the reservoir properties are controlled by diagenetic alterations and intense fracturing.